Keselarasan Pendidikan dengan Tingkat Perkembangan Anak - Siti Farikhah (Prodi PGMI IAIN Salatiga, 2009)
The existence of students at the same education level is likely similar in terms of their age; but actually, they are heterogeneous individuals. They have different mental, social, and emotional maturity, ability, interest, and their achievement. The difference demands different treatment and guidance. Accordingly, education orienting to the student development should be interpreted as the conscious efforts to prepare students referring to the individualized instruction principles, even though is accomplished classically. School institutions, in fact, commonly generalize and do not educate students based upon their characteristics to achieve their truly development. The question is why students look boring and reluctant to join a certain subject in very complicated and ambitious curriculum? It can be that they receive all immediately, while they are still unready to accept in a such development. What kind of process that can help their development? To do so, school institutions need the education process suitable with student development closely relating to physical and psychological development. This includes education that helps physical growth, cognitive and emotional development, creativity enhancement, aptitude, social relation development, as well as language and moral development.